The Relationship between Organizational Trust, Organizational Commitment and Perceived Organizational Support at the Ministry of Economic Affairs And Finance - Alireza Bahrami; Rasool Sarihi Asfestani (مطالعات مدیریت بهبود و تحول, 2015)
Success in competitive world requires the ability to develop trust-based relationships and is considered to be its key component. Accordingly, organizations and employees need to both be reliable and trust each other. And, organizational commitment is also an important occupational and organizational attitude which has been given the prime attention by the researchers of organizational behavior field. On the other, perceived organizational support indicates the employees’ perception regarding the extent of organization’s attention to their attempts, health, and peace. Hence, with respect to the importance of these factors in organizations, the present study examines the relationship between organizational trust, organizational multidimensional commitment, and perceived organizational support. Sample of the study consisted of the headquarters staff of deputy of financial supervision and bursary of the Ministry of Treasury and Economic Affairs (N=175). Stratified random sampling was applied and the sample size was gained as 120 employees based on Cochran’s formulae. To collect data, Clip Siwat et al (2012) questionnaire was used. Also, to enhance the validity of the questionnaire, the feedback from the elites of the field and experts of Ministry of Treasury and Economic Affairs were used. Chronbach’s alpha (0.84) was employed to determine the reliability of the questionnaire. Here, data analysis was carried out by means of correlation matrix, multi-regression equations, and SPSS. Results indicated that organizational trust (0.83) and perceived organizational support (0.653) Relationship organizational commitment And, organizational trust has significant Relationship on perceived organizational support (0.75). Exploiting these results organizations will be able to overcome their rivals in the modern ever-changing world.